Risk of Occupational Low Back Pain in Operating Room Staff. - Arora, Anu; Domadia, Priyanshi (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Low back pain is one of the most common occupational across the globe with social and commercial implications as it increases absenteeism, reduced concentration and efficiency of the work, hence affects the economic sector. Operating room staff, which includes surgeons, assistants, staff nurses and surgical technician, is one of the most affected occupations amongst the health care industry. Excessive work requirements and exhausting work hours combined with use of incorrect ergonomics have shown to have been associated with low back pain. Hence this research is used to identify physical and environmental risks associated with low back pain in operating room staff. Methodology: A cross-sectional survey using self-drafted pre-validated questionnaire, based on convenience sampling of about 70 operating room staff members were taken in this study. Results: 60% of the subjects who has filled the questionnaire have reported at least one episode of low back pain at some point in their career. Of that 83% subjects reported of having pain on working days. Conclusion: Excessive work load, the postural demand of the job, incorrect employment of ergonomics, decreased physical fitness, addictions, obesity etc. are all risk factors for occupational low back pain in operating room staff.